1997
DOI: 10.1007/s007050050239
|View full text |Cite
|
Sign up to set email alerts
|

Identification of amino acids involved in a serotype and neutralization specific epitope with in the s1 subunit of avian infectious bronchitis virus

Abstract: Localization of neutralizing, serotype specific epitopes of infectious bronchitis virus has been difficult because these epitopes are conformationally dependent. We identified amino acids involved in a serotype specific, conformationally dependent epitope by analysis of the S1 gene of 13 monoclonal antibody-neutralization-resistant mutants. Substitutions in the predicted amino acid sequence of these mutants were located at residues 304 and/or 386. Most of the substitutions at residue 304 were from threonine to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
106
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 19 publications
9
106
0
Order By: Relevance
“…The results confirmed that S1 protein and N protein play a major role in humoral and cellular immune responses, respectively, which were in accord with the previous investigations [23,26,36]. The immune efficacy of subunit vaccine rHBM-S1-N was better than that of subunit vaccines rHBM-S1 or rHBM-S1-N in humoral and cellular immune responses.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results confirmed that S1 protein and N protein play a major role in humoral and cellular immune responses, respectively, which were in accord with the previous investigations [23,26,36]. The immune efficacy of subunit vaccine rHBM-S1-N was better than that of subunit vaccines rHBM-S1 or rHBM-S1-N in humoral and cellular immune responses.…”
Section: Discussionsupporting
confidence: 81%
“…The S glycoprotein is post-translationally cleaved into S1 and S2 subunits [21]. S1 protein determines the antigenicity and immunogenicity of the virus and plays an important role in the induction of specific neutralizing antibody and hemagglutination inhibition antibody, tissue affinity and cell adsorption, which can induce the body to produce humoral immune response [22][23][24]. N protein plays an extremely important role in the replication and assembly of IBV with its good immunogenicity, which can induce the body to produce cellular immune response [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The arginine residue encoded by this codon in the ArkDPI field isolate and the predominant vaccine populations may be associated with a neutralizing epitope. Moore et al (1997) found that 13 of 14 neutralizing antibodyresistant mutants of ArkDPI had a change in codon 386. However, most of the resistant mutants also had a mutation in codon 304, and all of the resistant mutants with a histidine codon at position 386 (like minor subpopulations of vaccine A) also had a change in codon 304 not found in vaccine A.…”
Section: Discussionmentioning
confidence: 99%
“…The S1 and S2 domain of SARS-CoV S protein can be identified by sequence alignment with other coronavirus S proteins, especially with the more conserved S2 domain (8-10). The S protein is also the major antigenic determinant for coronaviruses (9,(11)(12)(13)(14). It has recently been demonstrated that the binding of the S1 domain to its receptor angiotensinconverting enzyme 2 (ACE2) on host cells is responsible for SARS-CoV entry into cells (15).…”
mentioning
confidence: 99%